Effectiveness of Simple Cooling Devices Based on Fans and Ice to Improve Thermal Comfort in Islamic Boarding School Dormitories (International Journal of Education and Literature, 2025)
This study aims to analyze the performance of a simple cooling device based on a fan and ice to improve thermal comfort in the female dormitory rooms of Pondok Pesantren Darunnaja, Bengkulu. The research used an experimental quantitative approach involving temperature and humidity measurements as well as perception data collected through Likert-scale questionnaires. The experiment was conducted in six dormitory rooms measuring 3 × 3 meters. The results indicated that the device was capable of reducing room temperature by approximately 3–5°C and increasing relative humidity to a moderate level. About 70% of respondents reported an improvement in thermal comfort after using the device. Although the cooling effect was not optimal, the fan-and-ice-based system proved effective in creating a more comfortable indoor thermal environment. This simple cooling technology is cost-efficient, energy-saving, and environmentally friendly, making it suitable for application in dormitory or low-cost housing environments.